Two Experts, One Goal: Collaborative Deprescribing in Psychiatry - Miller, Rebecca; Pavlo, Anthony J. (Current Psychiatry Reviews, 2018)
Background: Deprescribing, or the active reduction or elimination of psychiatric medications, requires close collaboration between physician and patient. Purpose: This article outlines the use of shared decision making, peer support, and relapse prevention strategies as key elements of successful deprescribing in people with psychiatric disorders who are interested in decreasing or stopping psychiatric medications. Drawing from existing literature and a recovery oriented care perspective, specific recommendations to create appropriate contexts for deprescribing including collaborative relationships, social support and rehabilitation for example. Conclusion: Deprescribing as an intervention requires care coordination and preplanning to provide the best supports for the person in recovery.
Keywords: psychiatric medication